Causes of discontinuity of blood donation among donors in Shiraz, Iran: cross-sectional study - Kasraian, Leila (São Paulo Medical Journal, 2010)
CONTEXT AND OBJECTIVE: The adequacy of blood depends on blood donation rates and numbers of blood donors. To prepare adequate blood supplies, it is essential to investigate the barriers and factors that stop individuals from donating. This study aimed to identify the causes of lapsed donation at our center. DESIGN AND SETTING: Cross-sectional study of volunteer blood donors in Shiraz, Iran. METHODS: We selected 850 donors who had donated between January 1, 2005 and June 1, 2005, but had not donated again by June 2008. The participants were recruited by letter and telephone, and were interviewed using a specially designed questionnaire that contained items on demographic characteristics, donor motivations and reasons for not returning to donate. We used the chi-square test to identify associations between lapsed donor characteristics and reasons for declining to donate. RESULTS: The greatest motivation for donation was altruism. The most frequent reasons for lapsed donation were lack of time because of work and self-exclusion for medical reasons. Among first-time donors, the most frequent reasons were unsuitability for donation and lack of time. CONCLUSIONS: The reasons for not returning to donate are varied and may correlate with demographic characteristics. In this study, the main reason for not returning was lack of time. Changing donation hours so that donors can donate after work, providing mobile teams at workplaces, and shortening the duration of the donation process may help increase repeat donation rates.